PENGEMBANGAN APLIKASI ALAT BANTU PENULISAN TEKS ARAB PADA LATEX BERBASIS WEB (STUDI KASUS HADITS RIYADHUS SHALIHIN IMAM NAWAWI BUKU 2) - Wamiliana, Ricky Andreas, Dwi Sakethi (SEMIRATA 2015, 2015)
The two fundamental guidances for muslems are Al Qur’an and Al Hadits. In this digital era, Al Qur’an can easily be found both in original and its translations, but not for Al Hadits. Therefore, in this research we develop a system for Al Hadits taken from Riyadhus Shalihin Imam Nawawi Book 2 using Latex. In the application user can easily find the file about the certain topics, both in Arabics and its translation in Indonesian. Kata kunci : Al Qur’an, Al Hadits, Riyadhus Shalihin, Imam Nawawi, Latex.